Transformation of Korean politics and administration : a 30 year retrospective - Im, Tobin; Berman, Evan (Bingley, U.K. : Emerald Publishing Limited, 2022)
Transformation of Korean Politics and Administration: A 30 Year Retrospective retraces critical junctures that were turning points in Korean history as seen from the historical path dependence theory. The 13 chapters explain the significant changes that have occurred in the major pillars of the Korean politics and administration system, helping readers understand the processes of how a 'premodern' society characterized by simplicity became a modern or even post-modern society characterized by multiple and complex operations. This volume gives rich insights to those who are eager to learn lessons from Korea's experiences, provide an additional understanding about temporal dimension of the described events and explore monarchic presidential power, the shifting of power to the legislative branch, the changing role of judiciary branch, government reform strategies, decentralization reform. The Public Policy and Governance series brings together the best in international research on policy and governance issues. Books within the series are authored and edited by experts in the field and present new and insightful research on a range of policy and governance issues across the globe.
Chapter 1. Introduction: A constantly growing economy -- Part I: Changes in the administrative environment -- Chapter 2. Changes in demographic structure -- Chapter 3. The wave of informatization -- Chapter 4. Changes in the occupational world -- Part II: Changes in the political administrative system -- Chapter 5. Democratization of the electoral system -- Chapter 6. The president and internal administartion -- Chapter 7. Administrative reform -- Chapter 8. Changes in capacity management methods -- Chapter 9. Change of power in the legislature -- Chapter 10. Changes in the judiciary -- Chapter 11. Local government and decentralization -- Part III: The next 30 years -- Chapter 12. Pessimistic scenario -- Chapter 13. Optimistic scenario: Middle-power nation -- Chapter 14. Prerequisites for the optimistic scenario: Trust in government.
Includes bibliographical references and index.
Keywords: Korea (South) -- Politics and government; Public administration -- Korea (South); Political Science -- History & Theory; Politics & government